Overexpression of an AP2/ERF Type Transcription Factor OsEREBP1 Confers Biotic and Abiotic Stress Tolerance in Rice - Jisha, V.; Dampanaboina, Lavanya; Vadassery, Jyothilakshmi; Mithöfer, Axel; Kappara, Saivishnupriya; Ramanan, Rajeshwari (PloS one, 2015)
AP2/ERF-type transcription factors regulate important functions of plant growth and development as well as responses to environmental stimuli. A rice AP2/ERF transcription factor, OsEREBP1 is a downstream component of a signal transduction pathway in a specific interaction between rice (Oryza sativa) and its bacterial pathogen, Xoo (Xanthomonas oryzae pv. oryzae). Constitutive expression of OsEREBP1 in rice driven by maize ubiquitin promoter did not affect normal plant growth. Microarray analysis revealed that over expression of OsEREBP1 caused increased expression of lipid metabolism related genes such as lipase and chloroplastic lipoxygenase as well as several genes related to jasmonate and abscisic acid biosynthesis. PR genes, transcription regulators and Aldhs (alcohol dehydrogenases) implicated in abiotic stress and submergence tolerance were also upregulated in transgenic plants. Transgenic plants showed increase in endogenous levels of α-linolenate, several jasmonate derivatives and abscisic acid but not salicylic acid. Soluble modified GFP (SmGFP)-tagged OsEREBP1 was localized to plastid nucleoids. Comparative analysis of non-transgenic and OsEREBP1 overexpressing genotypes revealed that OsEREBP1 attenuates disease caused by Xoo and confers drought and submergence tolerance in transgenic rice. Our results suggest that constitutive expression of OsEREBP1 activates the jasmonate and abscisic acid signalling pathways thereby priming the rice plants for enhanced survival under abiotic or biotic stress conditions. OsEREBP1 is thus, a good candidate gene for engineering plants for multiple stress tolerance.